2001
DOI: 10.1021/bi002776i
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structural and Dynamic Characterization of the Acid-Unfolded State of Apomyoglobin Provides Insights into the Early Events in Protein Folding,

Abstract: Apomyoglobin forms a denatured state under low-salt conditions at pH 2.3. The conformational propensities and polypeptide backbone dynamics of this state have been characterized by NMR. Nearly complete backbone and some side chain resonance assignments have been obtained, using a triple-resonance assignment strategy tailored to low protein concentration (0.2 mM) and poor chemical shift dispersion. An estimate of the population and location of residual secondary structure has been made by examining deviations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
295
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(315 citation statements)
references
References 51 publications
20
295
0
Order By: Relevance
“…Thus, it has been possible to define the conformational propensities of unfolded and partly folded apomyoglobin by NMR (32)(33)(34)(35). Interestingly, acid-unfolded apomyoglobin shows a propensity for non-native helical structure in a region that connects the D and E helices, as well as the native-like structure observed in the A and H helices, which had been predicted in the kinetic studies (34).…”
Section: Experimental Verification Of Modelsmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, it has been possible to define the conformational propensities of unfolded and partly folded apomyoglobin by NMR (32)(33)(34)(35). Interestingly, acid-unfolded apomyoglobin shows a propensity for non-native helical structure in a region that connects the D and E helices, as well as the native-like structure observed in the A and H helices, which had been predicted in the kinetic studies (34).…”
Section: Experimental Verification Of Modelsmentioning
confidence: 92%
“…Thus, it has been possible to define the conformational propensities of unfolded and partly folded apomyoglobin by NMR (32)(33)(34)(35). Interestingly, acid-unfolded apomyoglobin shows a propensity for non-native helical structure in a region that connects the D and E helices, as well as the native-like structure observed in the A and H helices, which had been predicted in the kinetic studies (34). The NMR studies of the conformational propensities of the various forms of apomyoglobin (32)(33)(34)(35) included determination of the relaxation parameters of the polypeptide chain to site-specifically determine the backbone dynamics in each of the states of the protein.…”
Section: Experimental Verification Of Modelsmentioning
confidence: 99%
“…States-Residual helicity is retained even under denaturing conditions because it was also observed in a highly polar region (E52-AEMKA-S58) in acid-unfolded and in urea-denatured apomyoglobin (45,50). Remarkably, this sequence, which includes helix D of apomyoglobin, has an even higher content of residual helix than helix H of apomyoglobin, which has been shown to have a very high intrinsic helix propensity in peptide studies.…”
Section: The Interactions Rendering Prp Helix 1 Stable Are Responsiblmentioning
confidence: 96%
“…It has been shown that i,iϩ4 hydrophobic interactions stabilize helices (28,45,46). PrP helix 1 contains a pair of i,iϩ4-spaced tyrosine residues in positions 145 and 149, respectively.…”
Section: [De]-x-x-a-[rk]-x-x-[rk]-[de] Modeling the D147a Mutation Anmentioning
confidence: 99%
“…Denatured proteins contain considerable amounts of native and non-native structure, both of which may provide information about early folding events [810]. Spectroscopic techniques such as nuclear magnetic resonance (NMR) allow the observation of residual structure in the denatured state of a number of proteins [11,12].…”
Section: Introductionmentioning
confidence: 99%